Pengembangan Buku Penuntun Praktikum IPA Terpadu Kelas VII Semester Ganjil Dengan Pemanfaatan Sumber Daya Alam Di Kabupaten Labuhan Batu Selatan - Rizky Ariaji; Andes Fuady Dharma Harahap (Jurnal Pendidikan Biologi, 2018)
This research aims to gain a practical guidebook on integrated SCIENCE Class VII semester odd with the utilization of the natural resources of South Labuhan Batu Regency. (1) the test to find out the feasibility of integrated SCIENCE practical guidebook on Class VII semester has developed an odd fit standard BSNP. (2) to find out the opinions of teachers and professors against the practical guidebook on integrated SCIENCE Class VII semester has developed an odd fit standard BSNP. The entire sample is selected by means of purposive sampling. Samples are defined in this study (1) Professor of biology, physics and chemistry University of Muhammadiyah South Tapanuli S2 education criteria amounted to 3 people. (2) integrated SCIENCE teachers in district of South Labuhan Batu Regency Torgamba from some schools with Undergraduate education criteria. The results of the deliberations of the research (1) to the average value of all aspects of the standard of eligibility based on the criteria of 4.30 BSNP is validitasnya { very valid and do not need revision (very decent)}. (2) the standard eligibility content was of 297 as well as an average rating of 4.30 by respondents lecturer and 613 and the average rating of 4.44 by the respondent teachers IPA. The standard language is the feasibility of 193 and an average rating of 4.29 by the respondents to the lecturer and 356 and the average value of 3.96 by respondents to the teachers of the IPA. The eligibility standards of presentation is of 206 as well as an average rating of 4.43 by respondents lecturer and 415 and the average rating of 4.32 by respondents to the teachers of the IPA. The eligibility standard kegrafikan is 476, as well as the average value of 4.29 by the respondents to the lecturer and 963 and the average rating of 4.34 by respondents to the teachers of the IPA.